Identification of Antibiotic-Resistance Genes from Lactic Acid Bacteria in Indonesian Fermented Foods - LINDA SUKMARINI; APON ZAENAL MUSTOPA; MARIDHA NORMAWATI; IKRIMAH MUZDALIFAH (HAYATI Journal of Biosciences, 2014)
Lactic acid bacteria (LAB) are known to have an important role in food fermentation and are thought to have health-promoting abilities such as probiotic properties. In this study, LAB were isolated from Indonesian fermented foods such as dadih (fermented buffalo milk), tempoyak (fermented durian), bekasam (fermented meat), and tape ketan (fermented glutinous rice). Those isolates were investigated for their resistance to two antibiotics: chloramphenicol and erythromycin. Recent efforts in food science have sought to identify genetic markers for antibiotic resistance within LAB strains, so that these genes can be selected for genetic modification. Such research is presently being directed toward the development of food-grade vectors (plasmid). The aim of this study is to screen LAB isolated from Indonesian traditional fermented foods, for chloramphenicol and erythromycin resistance. In this study, a total of 120 LAB samples were taken from traditional Indonesia fermented foods, and were tested for resistance to chloramphenicol and erythromycin. The results show that three LAB strains remained resistant to doses of up to 5 μg/mL chloramphenicol, while the LAB strain Lactobacillus plantarum showed resistance to the antibiotic erythromycin up to a concentration of 15 μg/mL.